(3TaGA GdCSbGe hOhGA GdBdGes - (3NVQ Hf Ydj Hf GdNWGH, MGLj HGTG,J (B800 (3g` s
(3ChdgG (B:s
(3bHjd LQH GdeKGfI hcPG eGA GdLHf ;dCfgeG jUQaJGf GdeGOI Edi LGfH GdCeYGA hjZSdGf GdYQhb s
(3BNQgG (B:s
(3hjgJe ai CeQ cd eQjV ,ceG jgJe ai MGd faSg ,dFdG jDOi JbUjQg Edi gdGceg heeGJg ,hjbhd GdLejd ai cd ef SGd Yf MGdg ef GdfGS , hjMJQR ajeG jbhdg Ch jMcjg ef GdEdJHGS s
(3QJHg Ydi CQHY ebGdGJs
(3hCgOGg dYjSi Hf eMeO Hf CHis
(3GdebGdI GdChdi ai cdjGJ LRFi GdWHs
(3hGdKGfjI ai GdCZPjI hGdCTQHI s
(3hGdKGdKI ai GdCeQGV GdeNJUI HYVh Ohf YVh ef GdQCS Edi GdbOe s
(3GdQGHYI ai GdCeQGV GdYGeI GdJi dG JNJU HYVh Ohf YVh s
Keywords: (3GdWHs